CURRENCY POLICY LIBERALIZATION IS AN IMPORTANT CONDITION FOR ECONOMIC GROWTH - Tokhirov, Jakhongir (Journal of Economics and Tourism Research, 2026)
This article analyzes the currency policy liberalization reforms implemented in Uzbekistan in 2017. Through these reforms, free access to foreign currency was granted to all entrepreneurs and individuals, bureaucratic barriers and sectoral privileges were abolished, and as a result exports and investments were stimulated, business activity increased, and overall economic prosperity was strengthened.